Consumer Lending in Theory and Practice - Teplý, Petr (Karolinum, 2016)
This book deals with consumer lending from both theoretical and empirical points of view. In the theoretical section, it book analyses the wider context of financial literacy, household indebtedness and the global consumer credit market including relevant legal, regulatory and risk management issues. In the empirical section, the book uses The Navigator of Responsible Lending as an evaluation tool to assess both bank and non-bank consumer credit providers in the Czech Republic. Although our empirical research is done as a case study on the Czech Republic, its basic ideas might be easily applied to other countries as well. Enclosures to the book include additional texts relevant to consumer lending (including case studies and an unofficial English translation of the Czech Consumer Credit Act) and therefore provide the reader with several perspectives on the topic.
Keywords: Ekonomie